Chemistry of the Chilean Strawberry (Fragaria chiloensis spp. chiloensis) - Schmeda Hirschmann, Guillermo (2011)
The Chilean strawberry (Fragaria chiloensis spp. chiloensis) is one of the progenitors of the cultivated strawberry, Fragaria × ananassa.Recent studies have started to disclose the chemical composition of the native fruit, the secondary metabolite occurrence and distributionin different plant parts as well as the biological activity of the main fruit constituents. This article revises the chemistry of the Chileanstrawberry and compares some of the most characteristic constituents with that of the highly cultivated and worldwide known F. ×ananassa. The main phenolic in the white strawberry are ellagic acid or hexahydroxydiphenolic acid-based hydrolysable tannins and procyanidinsas well as flavonoid glycosides from quercetin and kaempferol. The general trend in the plant is the accumulation of condensedtannins of increasing molecular weight in the rhizomes while the leaf contains mainly hydrolysable tannins and flavonoids.